Anti-Helicobacter Pylori, anti-thyroid peroxidase, anti-thyroglobulin and anti-gastric parietal cells antibodies in Czech population - Sterzl, I; Hrdá, P; Matucha, P; Čeřovská, J; Zamrazil, V (Physiological research, 2008)
Autoimmune thyropathies are frequently linked to many infections, such as Helicobacter pylori, which are also supposed to play a role in their pathogenesis. The aim of this study was to evaluate the relationships between thyroid and gastric autoimmunity and H. pylori infection on a large sample of Czech population (n=1621) by monitoring the autoantibodies against thyroglobulin (anti-Tg) and thyroid peroxidase (anti-TPO) and gastric parietal cell (anti-GPC, representing thyrogastric syndrome) in correlation with antibodies against Helicobacter pylori (anti-H. pylori) of classes IgG and IgA. The interrelation between autoantibodies and H. pylori antibodies was assessed by H. pylori seropositivity. In H. pylori seropositive persons as compared to seronegative irrespective of age and sex, a higher occurrence of anti-TPO (10.4 % vs. 5.8 %, p=0.001) and anti-GPC (6.1 % vs. 1.7 %, p<0.001) was found. Differences in anti-TPO occurrence were significant in both men (7.0 % vs. 3.3 %, p=0.03) and women (12.7 % vs. 8.0 %, p=0.02), differences in anti-GPC occurrence were significant only in women (7.2 % vs. 1.7 %, p<0.001). Results of this study support the idea of a connection between infection of H. pylori and the occurrence of anti-TPO autoantibodies representing thyroid autoimmunity and gastric parietal cells autoantibodies representing the thyrogastric syndrome.
Keywords: autoimunitní tyreoiditida; Autoantibodies; jodidperoxidasa; Humans; imunoglobulin G; dítě; Child; Female; protilátky bakteriální; dospělí; séroepidemiologické studie; lidé; žaludeční parietální buňky; Iodide Peroxidase; Immunoglobulin A; Antibodies, Bacterial; Parietal Cells, Gastric; Adult; Thyroglobulin; Thyroiditis, Autoimmune; ženské pohlaví; Helicobacter Infections; thyreoglobulin; Helicobacter pylori; Male; autoprotilátky; Seroepidemiologic Studies; Adolescent; Czech Republic; imunoglobulin A; Česká republika; mužské pohlaví; Immunoglobulin G; infekce vyvolané Helicobacter pylori; mladiství